PENGEMBANGAN BAHAN AJAR QIRO’AH DENGAN TEMA LINGKUNGAN BELAJAR UNTUK SISWA MTS JABAL AN-NUR PROVINSI LAMPUNG - Saeful Rahman; Rumadani Sagala; Erlina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
The purpose of this study was to develop Arabic teaching materials with the qiro'ah method, which is expected that students can more easily understand the material discussed and can improve reading skills of Arabic texts to be applied at the junior high school level. This research method is a research development or Research and Development (R&D) by taking the object of MTs Jabal An-Nur Lampung Province. The development is carried out in several stages, namely: potential and problems, data collection, product design, design validation, design improvement, product testing, and product revision. This development produces products in the form of Arabic teaching materials with the qiro'ah method through valid and appropriate development research and can be used in Arabic learning activities. From Arabic teaching materials using the qiro'ah method, it was found that after receiving Arabic teaching materials using the qiro'ah method it was easier to understand Arabic text material. Then, after using books from Arabic teaching materials with the qiro'ah method, students were able to work on the questions given. After being given Arabic teaching materials with the qiro'ah method, students became easier to understand the material discussed, and students were able to improve reading skills in Arabic texts.